2019
DOI: 10.1073/pnas.1915770117
|View full text |Cite
|
Sign up to set email alerts
|

A genetically defined disease model reveals that urothelial cells can initiate divergent bladder cancer phenotypes

Abstract: Small cell carcinoma of the bladder (SCCB) is a rare and lethal phenotype of bladder cancer. The pathogenesis and molecular features are unknown. Here, we established a genetically engineered SCCB model and a cohort of patient SCCB and urothelial carcinoma samples to characterize molecular similarities and differences between bladder cancer phenotypes. We demonstrate that SCCB shares a urothelial origin with other bladder cancer phenotypes by showing that urothelial cells driven by a set of defined oncogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 58 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…Immunofluorescence staining We used Ki67 antibody to determine the promotion effect of Cu 5.4 O on HUVECs [ 33 ]. HUVECs were seeded in 24-well plates (5 × 10 4 cells per well) and treated with 20 μL of Hep-PEG (3.2 wt%), Cu 5.4 O (16 ng μL −1 ), or Cu 5.4 O@Hep-PEG (3.2 wt%, Cu 16 ng μL −1 gel) for 24 h. Then, cells were permeabilized with Triton X-100 (Boster, China) and blocked with 10% goat serum (Boster, China).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining We used Ki67 antibody to determine the promotion effect of Cu 5.4 O on HUVECs [ 33 ]. HUVECs were seeded in 24-well plates (5 × 10 4 cells per well) and treated with 20 μL of Hep-PEG (3.2 wt%), Cu 5.4 O (16 ng μL −1 ), or Cu 5.4 O@Hep-PEG (3.2 wt%, Cu 16 ng μL −1 gel) for 24 h. Then, cells were permeabilized with Triton X-100 (Boster, China) and blocked with 10% goat serum (Boster, China).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent evidence supports the idea that SCCB originates from urothelial cells. How urothelial cells transdifferentiate remains elusive [138,140]. Possibly, anti-cancer treatments can induce the transdifferentiation of urothelial cells into tumors with a neuroendocrine phenotype in a similar manner as it has been described for neuroendocrine transdifferentiation of prostate adenocarcinoma upon androgen-deprivation therapy [141].…”
Section: Hedegaard Et Al Identified Three Molecular Subtypes Of Nmibmentioning
confidence: 95%
“…Neuroendocrine tumors comprise small cell carcinoma of the bladder (SCCB) and large cell carcinoma of the bladder (LCCB). SCCB is more prevalent than LCCB but is extremely rare, making up only 0.5% of BLCa, and it is usually diagnosed at late stages [138]. To date, no guidelines for the treatment of neuroendocrine tumors have been formulated.…”
Section: Hedegaard Et Al Identified Three Molecular Subtypes Of Nmibmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, developing precise diagnostic strategies and treatments are necessary. Though numerous previous studies have revealed several insights into the pathogenesis of BC, the underlying molecular mechanisms are largely unknown (3)(4)(5). To increase the diagnostic and therapeutic accuracy of BC, it is necessary to explore the underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%